METALES PESADOS EN EL SEDIMENTO DEL PUERTO DE SALAVERRY SETIEMBRE 2018 – FEBRERO 2019 - BERNAL TAY, Mercedes Elizabeth (2019)
The oceans are the final deposit of most substances discarded by man. Over time, biological activity favors the decomposition of organic compounds to carbon dioxide and water as the final product. The commissioning of port activities related to the movement of metals could affect the quality of the environment causing pollution by heavy metals, these are considered the most dangerous. Salaverry port place is the arrival of different vessels and mostly cargo, which carry and bring ore and these are transported in fine particles at different concentrations, which eventually settle into the sea. The main objective of this investigation was to determine the concentrations of heavy metals in the marine sediment of the port of Salaverry, three samplings of four stations and a target were performed respectively. An increase in arsenic, copper, mercury and lead was obtained in January and February with respect to November with a maximum of 43mg / kg in Arsenic, 62.4mg / kg in Copper, 0.342mg / kg in Mercury and 43mg / kg in lead; This may be due to dredging at the end of 2018 and also to different vessels with loads of different minerals.